LEADERSHIP CHARACTERISTICS in Addressing Construction Challenges - Nur Ain Ngah Nasaruddin; Ismail Abdul Rahman (2020)
Construction industry is one of the most important sectors in supporting economy growth and development of a country. However, the industry is also facing many issues that leads to construction project failure. It could be attributed from mishandling of challenges that emerged along the construction processes. These challenges issues are related to resources allocation, time, cost, quality, safety, project complexity, changes, uncertainties and also communication. It requires several approaches to handle these challenges effectively. There are many cases of projects failure due to poor leadership in handling construction challenges. Hence, this research book focus on leadership characteristics needed for Malaysia construction industry. The book has successfully uncovered significant leadership characteristics in facing the construction challenges.This book consisted of 4 chapters where the first chapter is regarding the leadership issues engulfing construction industry. While, the second chapter is about challenges that faced by construction practitioners in the project implementation and identifying the significant leadership characteristics which are need to handle the challenges. The third chapter is on developing structural model which relate the leadership characteristics with the construction challenges. Finally, the last chapter is on model’s verification and its application. This book is useful to researchers to explore leadership issues in construction industry and also for construction practitioners in evaluating their organizational leadership in handling challenges.